Trichomyia Haliday in Curtis (Diptera: Psychodidae) from southern Brazil: four new species and seven new records - Rossito, Lucas; Andrade, Andrey J.; Pinho, Luiz Carlos (Zootaxa, 2024)
The Neotropical region currently has the greatest richness of species in the genus Trichomyia Haliday in Curtis, but many regions, such as southern Brazil, have the fauna poorly explored. Here we describe four new species: Trichomyia brisolai sp. nov., T. aculeata sp. nov., T. marumbi sp. nov. and T. uncata sp. nov. and provide new records for seven brazilian species: T. inermis, T. brasiliensis, T. danieli, T. nocturna, T. riodocensis, T. truncata and T. mineira from the southern region of Brazil.